Educação física : realidade e possibilidades da prática pedagógica para o estudante trabalhador - Lira, Núbia Josania Paes de (2008)
The main object of this research is to investigate teaching practices in Physical Education for the education of teenagers and adults (EJA). To deal with this, it will be presented the politic and economic determinations related to the logic of capitalism and the influence of the student worker in education. Secondly, we intend to analyze the history of education of teenagers and adults which influences the educational policies. This will be followed by a discussion about the teaching practice of Physical Education for teenagers and adults in evening classes. In this research we understand Physical Education to be a knowledge essential to the formation of teenagers and adults, the majority of these characterized as student / worker mediated by the duality study / work. This dialectic is a result of the dualism present in a society controlled by ruling classes which dominate the means of production by taking advantage of the work force of the ones who sell it to be subservient to the logic of the capital. Then, we will overcome the social inequalities created by the capitalism that excludes from the world of employment the majority of the teenagers and adults in the country by giving them the excuse of lack of qualifications . We adopted a qualitative research of descriptive type to investigate and refute the hypothesis that teachings projects made for Physical Education do not contribute to an education to human freedom. The categories historic project and teaching practices were chosen. The research was conducted in seven public schools in the city of Aracaju which, together, contribute with 58% of the students enrolled in the EJA program. The data analysis shows the teaching practices and its contradictions, as the investigated schools are not influenced by the theoretical discussions linked with the university. In one hand, fortunately, it ignores the theories which don t occur in the educational environment, that is, in a relationship with the people involved in these practices. In the other hand, they don t either consider the relevant subject which would encourage the discussion between teachers that could bring relevant ideas. Finally, our historic aim is to take part in an insistent fight for the education of student workers, involved in a complex and contradictory life to which the contemporary society must consider, as these people still contribute a lot for the development of the country.